FIRST SERBIAN SOKOL SLET IN AMERICA IN 1912 (Fiep Bulletin - online, 2014)
Czech body workout system, better known as Sokol system, was founded in Czech Republic in 1862. Soon after it spread to all Slavic countries and other countries inhabited with Slavic people. That is how it came to area with Serbian people too. First Serbian Sokol societies in America started in the mid 1909, and their first meeting was held on 1st, 2nd and 3rd October in Gary (Indiana). At that meeting they formed Serbian Sokol Union in America and started the initiative for holding a First Serbian Sokol Slet (First Serbian Sokol competition) in America. Competition was held on June 22nd and 23rd 1912 in Chicago (Illinois) with presence of great number of spectators. Besides Serbian Sokols other Slavic Sokols have also participated, as also educational, gymnastics and charity societies. Different primary and secondary historical sources were reviewed and analyzed, most of all sources originated in the time of First Serbian Sokol Slet (competition), as also the ones originated later.
Keywords: Sokols; župa (union); Sokol societies; Sokol Slets (gatherings); competitions